Sewe heerlike homiletiese doodsondes. : Sondige insigte uit die kreatiewe skryfkuns en (Afrikaanse) letterkunde - Wepener, Cas (Stellenbosch Theological Journal, 2019)
Seven delectable homiletical deadly sins. Sinful insights from creative writing and (Afrikaans) literature Homiletics can learn much from Literature. Poets, novelists and short story writers are all masters of the written word. While they practise their art form, they very specifically keep their readers in mind. The same holds true for preachers with regard to both the spoken and written word. Through the ages writers of works of literature have employed a vast amount of rhetorical wisdom, insights they have gained from both language and literature, which they use in their stories, dramas and poems. In this chapter seven of these insights will be explored as insights from which preachers can benefit. This exploration is done by making use of the seven deadly sins, but in this article, they are deadly sins that preachers should commit week after week. This chapter is in that sense a plea for a harmatological Homiletics. Pride is the first step needed to a create hit. Greed with regard to the attention of the hearers should be committed boldly. A preacher who makes use of lust will unleash desire in the hearers and an angry preacher meets many hearers in the situation they currently find themselves. Preachers who are gluttons, swallow their hearers in their total being and an envious preacher inculturate the pulpit by means of meaningful intertextuality. And the best preachers are the lazy ones, because the show their rather than tell.